2020
DOI: 10.1027/2151-2604/a000414
|View full text |Cite
|
Sign up to set email alerts
|

Can Defense Attorneys Detect Forensic Confirmation Bias?

Abstract: Abstract. Knowledge of task-irrelevant information undermines the probative value of forensic evidence (i.e., forensic confirmation bias). Cross-examination may sensitize jurors to bias – but do attorneys recognize when bias has tainted evidence against their client and adjust their cross-examination strategy accordingly? To address this question, 130 defense attorneys imagined representing a man charged with manslaughter and reviewed a case file that included, among other things, an autopsy report from a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It is unlikely, however, that real world jurors would hear an examiner make such a concession. A recent study found that defense attorneys failed to recognize when confirmation bias had tainted evidence against their client, such that only 46% of attorneys who read a patently biased autopsy report asked the medical examiner about potential bias during cross-examination (67). Moreover, while many examiners recognize that cognitive bias can affect their peers, few believe that they are personally vulnerable to bias (i.e., a "bias blind spot;" [24][25]).…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely, however, that real world jurors would hear an examiner make such a concession. A recent study found that defense attorneys failed to recognize when confirmation bias had tainted evidence against their client, such that only 46% of attorneys who read a patently biased autopsy report asked the medical examiner about potential bias during cross-examination (67). Moreover, while many examiners recognize that cognitive bias can affect their peers, few believe that they are personally vulnerable to bias (i.e., a "bias blind spot;" [24][25]).…”
Section: Discussionmentioning
confidence: 99%
“…However, through "Figure 1", it is clear that our depression level does have some impact on our level of confirmation bias. People with confirmation bias tend to seek and select the information that confirms their previous beliefs, and ignore all the disadvantaged information that comes to them [1]. People with depression have higher level of anxiety, that cause people to have sleeping problems, and difficulties on concentration, which will lead them to seek the information that is confirming their preexisting belief [13].…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation bias is what all the human being had, and is what that help persist people's belief and keep helping people to reach the goal they want eventually. A confirmation bias is the tendency to seek, select, or to interpret the information that is confirmed through human's pre-existing belief, and this phenomenon is ubiquitous [1]. In other word, confirmation bias is the tendency to interpret the information in a way that confirms one's preexisting belief.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Attorneys are expected to identify risks that could jeopardise their clients' interests, but their role in detecting forensic bias has largely been neglected in today's literature. Despodova, Kukucka, and Hiley (2020) took on this understudied topic by assessing whether defense attorneys can detect if an autopsy report from a medical examiner had been tainted by knowledge of the defendant's recanted confession. Defense attorneys appeared insensitive to the possibility of biased forensic reporting.…”
Section: Editorialmentioning
confidence: 99%